Central Corneal Thickness and Intraocular Pressure Measured with Goldmann Applanation Tonometer among Patients with Normal Intraocular Pressure - Singh, Pranisha; karmacharya, Srijana; Rizyal, Aparna (Journal of Nepal Health Research Council, 2025)
Background: Intraocular pressure measurement is one of the important and commonly performed examination in Ophthalmology. Goldmann applanation tonometer has been gold standard for measurement of Intraocular pressure. Intraocular pressure measurement is known to be affected by Central corneal thickness. It has been stated that thinner cornea leads to false low Intraocular pressure while thicker cornea leads to false high Intraocular pressure interpretations.Methods: A total of 920 patients of forty and above years with no any anterior segment pathology like corneal diseases, corneal oedema and opacities, uveitis, ocular surgery, ocular trauma or evidence of glaucoma were included. This was cross sectional, descriptive, hospital based study. Ultrasonic pachymeter was used to measure Central corneal thickness and Goldmann applanation tonometer was used to measure Intraocular pressure. A correction factor was applied and corrected Intraocular pressure values were calculated.Results: The mean Central corneal thickness was 538.70 ± 29.17 µm and Intraocular pressure was 14.72 ± 2.58 mmHg. The mean Central corneal thickness of the females was thinner and mean corrected Intraocular pressure was higher than male. There were statistical significant differences in the mean Central corneal thickness and corrected Intraocular pressure between genders (p= 0.029, p=0.04) respectively. There was a significance difference in mean Central corneal thickness between different age groups (p= <0.001). Corrected Intraocular pressure is negatively correlated with Central corneal thickness (r= - 0.49, p= <0.001). In this study there was a significant association between Central corneal thickness and Intraocular pressure, age, gender and refractive error. Conclusions: A thick cornea leads to an overestimation of Intraocular pressure while thin cornea leads to an underestimation of Intraocular pressure. We recommend that Intraocular pressure measurement should be associated with a pachymetry correction to avoid inaccurate readings.Keywords: Central corneal thickness; corrected intraocular pressure; intraocular pressure.